2016
DOI: 10.1002/14651858.cd011421.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Single dose dipyrone (metamizole) for acute postoperative pain in adults

Abstract: Based on very limited information, a single dose of dipyrone 500 mg provides good pain relief to about 70% of people treated, compared to about 30% with placebo. For every five people given dipyrone 500 mg, two people would experience this level of pain relief over four to six hours who would not have done with placebo, and fewer people would need rescue medication.We were unable to compare dipyrone directly with other active treatments, or to assess the effects of different doses or routes of administration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 58 publications
(20 reference statements)
1
35
0
6
Order By: Relevance
“…A recent study, which especially focused on the probability of serious ADRs in children, identified the problem of sufficient sample sizes and follow‐up needed to detect agranulocytosis . This same problem was noted in the Cochrane review on the efficacy and adverse events of a single dose of dipyrone for acute postoperative pain in adults, in which no serious adverse events were shown . Although agranulocytosis is a serious condition, it should be considered in comparison with other potentially life‐threatening adverse effects of analgesics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study, which especially focused on the probability of serious ADRs in children, identified the problem of sufficient sample sizes and follow‐up needed to detect agranulocytosis . This same problem was noted in the Cochrane review on the efficacy and adverse events of a single dose of dipyrone for acute postoperative pain in adults, in which no serious adverse events were shown . Although agranulocytosis is a serious condition, it should be considered in comparison with other potentially life‐threatening adverse effects of analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the analgesic efficacy of a single 500 mg oral dose of dipyrone appears similar to that of ibuprofen 400 mg, while a single 2.5 g intravenous dose appears equivalent to 100 mg intravenous tramadol . These results were recently withdrawn because the same authors concluded that the data used were insufficient to support former conclusions and so were unable to compare dipyrone directly with other analgesics …”
Section: Introductionmentioning
confidence: 99%
“…Metamizole is available for oral, rectal, and intramuscular administration. Due to its good solubility in water, it can also be administered intravenously . While metamizole can be detected in the plasma for approximately 15 minutes after intravenous administration, it is nearly untraceable after oral administration .…”
Section: Hepatic Metabolism Of Metamizolementioning
confidence: 99%
“…A single‐site analysis in a US urban pediatric hospital revealed that over one‐third of all Spanish‐speaking Latino families had used metamizole before . Therefore, metamizole has received the (politically incorrect) nickname “Mexican aspirin” in some regions of the United States …”
mentioning
confidence: 99%
See 1 more Smart Citation